ANALYSIS OF STUDENTS' CRITICAL THINKING ABILITY IN SOLVING MATHEMATICS PROBLEMS IN CLASS XI AKL 1 SMK NEGERI 4 MAKASSAR - Arhy Wibowo Hikmal; Nana Harlina Haruna; Marilyn Lasarus (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to describe students' critical thinking skills in solving math problems for class XI AKL 1 SMK Negeri 4 Makassar in the matter of a system of two-variable linear equations using word problems. The research method is descriptive with a qualitative and quantitative approach. The subject of this research was taken 4 students namely 2 students with high critical ability and 2 students with low critical ability from 34 students of class XI AKL 1 SMK Negeri 4 Makassar. The process of critical thinking skills in solving math problems students who have high critical thinking skills can solve problems because they have previously understood the material and examples of questions given, and worked carefully and thoroughly. While students with low critical thinking skills still do not understand the material and examples of questions given by researchers so that in solving math problems there are several steps to solving them that they do not understand